Treatment Emergent Suicidal Ideation in depressed older adults. (9th May 2016) - Cristancho, Pilar; O'Connor, Brendan; Lenze, Eric J; Blumberger, Daniel M.; Reynolds, Charles F; Dixon, David; Mulsant, Benoit H.
Abstract : Background: Treatment‐Emergent Suicidal Ideation (TESI) in older adults is poorly understood. We characterized TESI in older depressed adults during treatment with venlafaxine and explored whether TESI is related to antidepressant exposure versus dimensions of the psychiatric illness. We examined the relationship among medication exposure, onset of TESI, and clinical characteristics. Methods: We analyzed data on 233 clinical trial participants with major depression and no baseline suicidal ideation who were treated for up to 12 weeks with venlafaxine XR (target dose: 150–300 mg/day). Suicidal ideation was assessed weekly with the Scale for Suicide Ideation. A Kaplan‐Meier curve displayed the time course of TESI. Differences in baseline demographic and clinical variables between the TESI and Non‐TESI groups were assessed with analyses of covariance or logistic regression. A final multivariate logistic regression model indicated baseline predictors of TESI. Depression treatment outcomes in subjects developing TESI versus those who did not were examined with a mixed effects model. Results: TESI occurred in 10% of participants, typically with onset within 4 weeks of the start of treatment. Anxiety, and depression severity at baseline were predictors of TESI. Most TESI was mild and transient, with 6/233 participants having TESI considered clinically meaningful. TESI was not associated with venlafaxine blood levels or side effects. Conclusions: In older depressed adults, TESI is relatively uncommon and it is likely related to the underlying illness rather than to a medication adverse effect. This suggests that TESI requires continuing rather than discontinuing antidepressant treatment. Copyright © 2016 John Wiley & Sons, Ltd.